Towards a Gendered Political Economy
XII, 261 p.
Keywords: This collection sets out how a gendered approach to political economy can help us understand the inherently gendered structures that characterise our society, and provide the foundation for a truly interdisciplinary social science. It provides a comprehensive coverage of gendered political economy - what it is, where it is and, perhaps more importantly, how it should develop. The twelve chapters that make up this volume combine the development of a theoretical framework with empirical examples, which illustrate the core concerns of gendered political economy.